The Correlation between Students’ Learning Motivation and Their Listening Comprehension - Rumi Susanti; N. Nurdiana (Indonesian Journal of Integrated English Language Teaching, 2018)
Based on the preliminary research, it was found that the eleventh grade students at senior high school 1 Kateman Indra Giri Hilir get difficulties in listening. It can be seen some of students were not able to express their ideas of speaker. The aimed of the research was to find out the correlation students’ learning motivation and their listening comprehension of the second grade at the senior high school 1 Kateman Indra Giri Hilir. The design of this research was correlational research design. The population  was the second grade students at Senior High School 1 Kateman Indra Giri Hilir. Because of large, the researchers took the sample was selected by using simple random sampling technique. In  getting the data, the researchers gave questionnaire and test, and  analyzing   the data by using person product moment calculated by SPSS 16.0 program. After analyzing the data, the result of sig.t.0.000 is smaller than 0.05 (sig≤0.05). It could be stated that Ha (alternative hypothesis) was accepted. In other words, there was a significant correlation between students’ learning motivation and their listening comprehension of the Senior High School 1 Kateman Indra Giri Hilir.